Implementation of 5S Work Culture (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) at Yogo Nouen Farm Hokkaido, Japan - Ardiyansah, Rizal (Program Studi Agribisnis UIN Syarif Hidayatullah Jakarta, 2024)
ABSTRACTThis study aims to analyze the application of 5S work culture at Yogo Nouen Farm on each variable, namely seiri, seiton, seiso, seiketsu, and shitsuke. The type of research used is qualitative research with the data sources being primary data and secondary data obtained through observation, interviews, documentation, and literature studies. The research informants used are key informants, namely the Head of Part II and the Head of Farmers and supporting informants, namely Foreign Workers from Indonesia, Vietnam, Cambodia, and Nepal. The data processing method used is the Miles and Huberman Model with the data validity technique is source triangulation and triangulation method as well as member check and reliability test is using the NVIVO 12 application. The result of this study is that from all measurements of the implementation of the 5S work culture, namely seiri, seiton, seiso, seiketsu, and shitsuke, two variables were found that have not been implemented properly, namely the seiketsu variable and the shitsuke variable. In the variable of seketsu, it is indicated that there has been no marking or labeling of dangerous goods or equipment and warnings to be careful in the work area. The shitsuke variable is indicated by the number of employees who have not complied with the predetermined regulations.Keywords: implementation; work culture; 5SABSTRAKPenelitian ini bertujuan untuk menganalisis penerapan budaya kerja 5S di Yogo Nouen Farm pada masing-masing variabel yaitu seiri, seiton, seiso, seiketsu, dan shitsuke. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan sumber data berupa data primer dan data sekunder yang diperoleh melalui observasi, wawancara, dokumentasi, dan studi pustaka. Informan penelitian yang digunakan adalah informan kunci yaitu Kepala Bagian II dan Kepala Petani serta informan pendukung yaitu Tenaga Kerja Asing (TKA) asal Indonesia, Vietnam, Kamboja, dan Nepal. Metode pengolahan data yang digunakan adalah Model Miles dan Huberman dengan teknik keabsahan data yaitu triangulasi sumber dan triangulasi metode serta member check dan uji reliabilitas menggunakan aplikasi NVIVO 12. Hasil penelitian ini adalah dari seluruh pengukuran penerapan budaya kerja 5S yaitu seiri, seiton, seiso, seiketsu, dan shitsuke ditemukan dua variabel yang belum terlaksana dengan baik yaitu variabel seiketsu dan variabel shitsuke. Pada variabel seketsu terindikasi belum adanya penandaan atau pelabelan barang atau peralatan berbahaya serta peringatan untuk berhati-hati di area kerja. Variabel shitsuke terindikasi dari banyaknya karyawan yang belum menaati peraturan yang telah ditetapkan.Kata kunci: penerapan; budaya kerja; 5S